2021
DOI: 10.3389/fphys.2021.597449
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29c Acting on FOS Plays a Significant Role in Nonalcoholic Steatohepatitis Through the Interleukin-17 Signaling Pathway

Abstract: Nonalcoholic fatty liver disease is the most common hepatic disease in western countries and is even more ubiquitous in Asian countries. Our study determined that TH17/Treg cells were imbalanced in animal models. Based on our interest in the mechanism underlying TH17/Treg cell imbalance in nonalcoholic fatty liver mice, we conducted a joint bioinformatics analysis to further investigate this process. Common gene sequencing analysis was based on one trial from one sequencing platform, where gene expression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It has been reported that one of such factors Gata4 could activate heart regeneration in zebrafish and mice [16,17]. In regulatory networks of NASH, we identified Fos and Klf6, which regulate TH17/Treg cells in NASH patients and are up-regulated in the context of steatohepatitis, respectively [18,19].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been reported that one of such factors Gata4 could activate heart regeneration in zebrafish and mice [16,17]. In regulatory networks of NASH, we identified Fos and Klf6, which regulate TH17/Treg cells in NASH patients and are up-regulated in the context of steatohepatitis, respectively [18,19].…”
Section: Discussionmentioning
confidence: 89%
“…When both scRNA-seq and ATAC-seq data are used, a much higher fraction of known transcription factors is identified by IReNA. For instance, in analysis of NASH samples, we identified Fos and Klf6, which regulate TH17/Treg cells in NASH patients and are up-regulated in the context of steatohepatitis, respectively [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 116 In mice on a high cholesterol diet, miR-125b-5p promoter methylation in liver was increased and its expression was reduced, leading to liver fibrosis via integrin α8 (ITGA8). 117 In addition, other miRNAs such as miR-137-3p, 118 miR-103, 119 miR-21, 120 , 121 miRNA-130b-5p, 122 miRNA-27a, 123 miRNA-29c, 124 miRNA-103, 125 miRNA-146b, 126 miRNA-33, 127 miRNA-7a, 128 and miRNA-451 129 are also associated with fatty liver disease caused by metabolic disorders.…”
Section: Epigenetics In Mafldmentioning
confidence: 99%
“…Overexpression of miR-195 can maintain the balance of Th17/Treg to ameliorate NAFLD and liver inflammation. Many miRNAs can regulate Th17/Treg cell balance in NAFLD such as miR-29c via interacting with insulin-like growth factor binding protein 1/IGFBP1)[ 55 ]. In addition, other microRNAs such as miR-155[ 56 , 57 ], miR-423-5p[ 58 ], and miR-1246[ 59 ] play important roles in modulating the balance of Tregs with Th17 cells and their functions in liver disease.…”
Section: Important Molecules Mediated Treg Function and Metabolismmentioning
confidence: 99%